Designing a PMRI Electronic Pocketbook for Enhanced Algebra Conceptual Understanding and Learning Interest in Junior High School Students - Atikah Fitriani; Jailani Jailani (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study aims to develop electronic pocketbooks based on PMRI (the Indonesian adaptation of realistic mathematics education) tailored to enhance concept comprehension and stimulate interest in learning algebra among seventh-grade students. The pocketbooks are designed to meet the standards of validity, practicality, effectiveness, and feasibility for use in educational settings. The research follows the ADDIE development model, which includes stages of analysis, design, development, implementation, and evaluation. The study was conducted with 32 seventh-grade students at a junior high school in Yogyakarta. Data collection methods included tests and questionnaires. The findings indicate that the electronic pocketbooks are highly valid, practical, and effective. Therefore, it can be concluded that the PMRI electronic pocketbooks, oriented towards improving conceptual understanding and learning interest in junior high school students, satisfy the criteria of being valid, practical, effective, and feasible for educational use. Consequently, these pocketbooks have the potential to significantly enhance mathematics education by accommodating individual learning styles, promoting a deeper understanding of algebra, and improving overall academic performance among junior high school students.